2022
DOI: 10.3389/fimmu.2022.845974
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, Pyroptosis, and Ferroptosis Conspiringly Induce Immunosuppressive Hepatocellular Carcinoma Microenvironment and γδ T-Cell Imbalance

Abstract: Hepatocellular carcinoma (HCC) is highly malignant and prone to metastasize due to the heterogeneous and immunosuppressive tumor microenvironment (TME). Programmed cell deaths (PCDs) including apoptosis, ferroptosis, and pyroptosis routinely occur in the HCC TME and participate in tumorigenesis. However, how apoptosis, ferroptosis, and pyroptosis are involved in constructions of the immunosuppressive TME and their underlying cross-talk remains to be further unveiled. In this work, we deciphered the immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, many studies have found that ferroptosis and apoptosis are closely linked, that apoptosis can be converted into ferroptosis under certain conditions, and that ferroptosis promotes cell sensitivity to apoptosis [ 26 , 27 ]. Hu et al found that apoptosis, pyroptosis, and ferroptosis together induced an immunosuppressive hepatocellular carcinoma microenvironment and γδ T-cell imbalance [ 28 ]. Our HE, TEM, and SEM results showed that CTX causes thymus injury, which is mainly manifested by the indistinct cortex and medullary demarcation of the thymus and reduced cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have found that ferroptosis and apoptosis are closely linked, that apoptosis can be converted into ferroptosis under certain conditions, and that ferroptosis promotes cell sensitivity to apoptosis [ 26 , 27 ]. Hu et al found that apoptosis, pyroptosis, and ferroptosis together induced an immunosuppressive hepatocellular carcinoma microenvironment and γδ T-cell imbalance [ 28 ]. Our HE, TEM, and SEM results showed that CTX causes thymus injury, which is mainly manifested by the indistinct cortex and medullary demarcation of the thymus and reduced cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, cancer-associated fibroblasts (CAF), another abundant cell type in the TME, facilitate tumor growth and metastasis through inflammasome signaling, a process attenuated when NLRP3 or IL-1β is specifically ablated [ 182 ]. In liver cancer, transcriptomic data from HCC samples indicate a highly immunosuppressive TME and upregulated markers for apoptosis, ferroptosis, and pyroptosis are associated with poorer survival [ 183 ]. However, it remains unclear how pyroptosis precisely affects biological processes in the TME of HCC and contributes to a pro- or anti-immunogenic TME.…”
Section: Cell Death In Liver Diseasementioning
confidence: 99%
“…It not only restrains the activity of antitumor immune cells and compromises the antitumor immunity, but causes the reversal of immunosuppression through the functional regulation of immunosuppressive immune cells ( Cong et al, 2022 ). It is reported that ferroptosis-related genes are associated with infiltration of protumor immune cells and expressions of inhibitory checkpoint molecules, indicating the involvement of ferroptosis in construction of the immunosuppressive TME in HCC ( Hu Y. et al, 2022 ). Similarly, HBV infection facilitates HCC cells to secrete the exosome miR-142-3p, which decreases the expression of SLC3A2 and further induces ferroptosis in M1 macrophages, accelerating the progression of HCC ( Hu Z. et al, 2022 ).…”
Section: Ferroptosis In Hccmentioning
confidence: 99%